2009
DOI: 10.2353/ajpath.2009.090157
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Insulin Signaling, Glucose Transporters, O-GlcNAcylation, and Phosphorylation of Tau and Neurofilaments in the Brain

Abstract: Recent studies have suggested a possible role of insulin dysfunction in the pathogenesis of sporadic Alzheimer's disease (AD). In AD, brain glucose metabolism is impaired, and this impairment appears to precede the pathology and clinical symptoms of the disease. However, the exact contribution of impaired insulin signaling to AD is not known. In this study, by using a nontransgenic rat model of sporadic AD generated by intracerebroventricular administration of streptozotocin , we investigated insulin signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
150
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(170 citation statements)
references
References 67 publications
15
150
0
5
Order By: Relevance
“…These changes could be speculated to be caused by a decreased stability and/or increased degradation of IDE protein since they have not been associated with changes in IDE mRNA expression which remained unchanged in this acute phase, although we have not measured IDE activity which might be changed as well. Our data are in line whit Deng et al (2009) who has demonstrated decrement in the expression of IDE protein and its activity in HPC 3 weeks after the STZ-icv treatment.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…These changes could be speculated to be caused by a decreased stability and/or increased degradation of IDE protein since they have not been associated with changes in IDE mRNA expression which remained unchanged in this acute phase, although we have not measured IDE activity which might be changed as well. Our data are in line whit Deng et al (2009) who has demonstrated decrement in the expression of IDE protein and its activity in HPC 3 weeks after the STZ-icv treatment.…”
Section: Discussionsupporting
confidence: 77%
“…Decreased p/t GSK-3ß ratio has been reported in a period up to 1 month after the STZ-icv treatment by others as well (Deng et al 2009;Shonsey et al 2012;Young et al 2014). However, in our experiments, this GSK-3β activation has not resulted in increased tau protein phosphorylation (PHF1) at this time-point when decreased p/t tau ration was found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phosphorylation status in Nrl Ϫ/Ϫ mouse retina was set at 100%. deficient brain insulin signaling pathway in Alzheimer disease and diabetes has recently been reported (75,76).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these observations, our understanding of the physiological role of O-GlcNAcylation in modulating brain function remains remarkably limited. To date, only a handful of studies exist examining O-GlcNAcylation in the nervous system, with most focusing on the relationship between decreased O-GlcNAcylation and hyperphosphorylation of tau in Alzheimer's disease (AD; Yuzwa et al, 2008;Deng et al, 2009;Yuzwa and Vocadlo, 2009). Because synaptic efficacy is highly regulated by serine/threonine phosphorylation/dephosphorylation of synaptic proteins (Malenka and Bear, 2004), it is possible that O-GlcNAcylation, which also occurs on serine/threonine residues, is as important as phosphorylation in modulating synaptic function.…”
Section: Introductionmentioning
confidence: 99%